Pengaruh net profit margin, return on asset, dan return on equity terhadap pertumbuhan laba - Zahra Rahma Fauziah; Astrin Kusumawardani; Listri Herlina (Jurnal Pengetahuan dan Pendidikan, 2026)
This research was driven by the existence of a research gap between academic theory and empirical facts regarding the fluctuations in profit growth within the food and beverage industry listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. The primary problem highlighted is the uncertainty surrounding the effect of internal financial performance indicators on profit growth amid intense market competition. To address this problem, the study utilized a quantitative method with descriptive and verificative approaches. A purposive sampling technique was applied, yielding 22 qualified companies and resulting in 88 observation data points over the four-year period. Multiple linear regression analysis utilising SPSS 26.0 software and traditional assumption tests were used to analyse the data. The scientific findings revealed that simultaneously (F-test), Net Profit Margin (NPM), Return on Asset (ROA), and Return on Equity (ROE) significantly influenced profit growth, contributing to a determination coefficient of 25.7%. Partially (t-test), NPM was proven to have a positive and significant effect, indicating that profit efficiency from sales acts as the main driver of profit growth. Conversely, ROA demonstrated no effect on profit growth, while ROE surprisingly exerted a negative and significant influence. The conclusion emphasizes that a high equity ratio without strict cost efficiency tends to suppress net profit growth, therefore management is advised to prioritize operational cost efficiency to sustain profit margin stability.